The spectrum of embodied intersubjective synchrony in empathy: from fully embodied to externally oriented engagement in Parkinson's disease - Zepeda, Antonia; Troncoso, Alejandro; Pizarro, Daniela; Baquedano, Constanza; Gomez, Rodrigo; Barria, Silvia; Blanco, Kevin; Martínez-Pernía, David (Frontiers in Psychology, 2025)
BackgroundParkinson's disease is a prevalent neurodegenerative disorder that not only affects motor function but also impairs empathy. While the neurobiological changes underlying these deficits are known, the impact of PD on the lived experience of empathy remains poorly understood. This study investigates the lived experience of empathy for pain in individuals with PD, with a specific focus on embodied intersubjective synchrony.MethodForty-five patients with mild to moderate PD were exposed to videos of athletes suffering falls during extreme sports. Following exposure, participants underwent phenomenological interviews to explore their embodied experiences in connection with the other's suffering. Data were analyzed through an iterative process involving three independent analyses, triangulation, and the application of advanced analytical techniques (CAQDAS, inter-rater agreement index, interactive dashboards, spider graphs) to enhance the depth of the phenomenological analysis.ResultsThis study provides a nuanced view of empathy for pain in Parkinson's disease, uncovering a spectrum of embodied intersubjective synchrony. Two primary empathic structures emerged: Embodied Resonance Empathy, marked by strong bodily and emotional connections with temporal synchronization to others' suffering through internal sensations, and Marginal Embodied Resonance Empathy, where bodily and emotional resonance is reduced or absent, relying mainly on external visual cues. Substructures of Embodied Resonance Empathy include Other-Centered Empathy, driven by a motivation to help, and Self-Centered Empathy, focused on personal discomfort. For Marginal Embodied Resonance Empathy, substructures range from Transparent Resonance Empathy, involving emotional responses without bodily sensations, to Non-Resonance Empathy, characterized by a complete absence of bodily and emotional resonance.ConclusionThis study uncovers a spectrum of embodied intersubjective synchrony in empathy among individuals with PD, ranging from fully embodied synchrony, characterized by internal bodily and emotional resonance, temporally attuned to the other's suffering, to externally oriented synchrony, characterized by diminished or absent bodily and emotional resonance, relying primarily on external visual alignment with the other's suffering. These findings highlight the importance of embodied intersubjective synchrony in empathy, suggesting that targeted interventions could be essential for enhancing social cognition in PD.